Hardware verification with C++ : a practioner's handbook. - Mintz, Mike, ....-; Ekendahl, Robert, ....- (New York : Springer, 2006)
Written by two verification engineers, "Hardware Verification with C++: A Practitioner's Handbook" is a four-part tour of how to perform object-oriented techniques. This handbook goes beyond hype and theoretical discussions to show fully implemented examples, all provided as open-source code on the companion CD. Part I makes the case for C++, and shows a standard verification system using object-oriented programming (OOP). Part II presents two open-source C++ libraries that enable efficient verification with C++ - Teal, a C++ to Verilog interface, and Truss, a standard verification framework. Part III focuses on OOP with examples from real verification projects. Part IV puts it all together showing complete block-level and system-level verification systems. Both a learning and a reference tool, "Hardware Verification with C++: A Practitioner's Handbook" gives you everything you need to do hardware verification with C++ apart from a simulator, all provided as open-source on the companion CD.
Keywords: Digitale elektronica; Logische schakelingen